Spin manipulating stored 1.85 GeV/c vector and tensor polarized spin-1 bosons - V. S. Morozov; A. D. Krisch; M. A. Leonova; R. S. Raymond; D. W. Sivers; V. K. Wong; R. Gebel; A. Lehrach; B. Lorentz; R. Maier; D. Prasuhn; A. Schnase; et al. (Physical Review Special Topics. Accelerators and Beams, 2005)
We recently studied the spin manipulation of 1.85  GeV/c vertically polarized deuterons stored in the COSY cooler synchrotron. We adiabatically swept an rf dipole’s frequency through an rf-induced spin resonance and observed its effect on the deuterons’ vector and tensor polarizations. After optimizing the resonance crossing rate and maximizing the rf dipole’s voltage, we measured spin-flip efficiencies of 97±1% and 98.5±0.3% in two separate runs. We also confirmed at higher energy the striking behavior of the spin-1 tensor polarization recently found at IUCF.